Flirting with Controversy: Making Biopics about Truman Capote - Delphine Letort (Revue LISA)
Based on a close study of the biopics devoted to writer Truman Capote, this article questions the expectations raised by films that feed on the voyeuristic desire to see into the personal lives of famous people beyond their public image. While literary biopics usually recreate the image of an author by drawing on his/her literary creations as signifiers of their authorial identity, Capote (Bennett Miller, 2005) and Infamous (Douglas McGrath, 2007) exploit the celebrity status of the writer by promoting his controversial lifetime achievement, In Cold Blood. Highlighting Truman Capote’s social life as a source of entertainment, the two films marginalize an author whose popularity overshadowed his literary achievements (including as a screenwriter).